User-Centered Change Management Process for CPOE Implementation - Almoaber, Basmah Mohammed (Université d'Ottawa / University of Ottawa, 2021)
In response to a changing world, the healthcare domain is transforming to become increas-ingly digital. Technology is introduced to address healthcare challenges such as rising healthcare costs, ageing population, and adverse events. One of the significant examples of digital healthcare transformation is the implementation of Computerized Provider Order Entry (CPOE). CPOE is a system in which orders are placed electronically by providers and then transmitted directly to the recipient. The implementation of a CPOE system is a challenging process for any healthcare organization. It requires a dramatic change not only to the way care is provided but also to the way clinicians work. The complexity of the CPOE system implementation emanates from the need to manage the people side of the project and convince them to change their behaviours to use the system and generate re-sults. Considering a CPOE system implementation project as successful requires the tech-nology to work on time and within budget, together with users changing their behaviours and effectively using the new system to its full potential. Typically, organizations’ primary focus during the CPOE system implementation is on technology implementation rather than being a strategic focus on users. The literature includes many articles that emphasize the importance of involving users, physicians in par-ticular, during every step of the CPOE implementation and how this involvement is neces-sary for the implementation success. However, most, if not all the articles, are considering users’ participation during the design phase of the system and not during the change man-agement plan development. Even if users’ involvement during the change is mentioned, there is no exact way to attain this involvement, and the principles that govern this involve-ment remain imprecise and difficult to operationalize. Healthcare organizations need a step-by-step CPOE change management guidance (a roadmap) that considers the needs and re-quirements of end-users to gain their acceptance of the system and realize its maximum benefits. To prepare users for the change and enhance their acceptance of the CPOE system, this thesis introduces a new User-Centered Change Management (UCCM) process. This process aims to create an appropriate environment for healthcare organizations to success-fully implement a CPOE system and achieve meaningful transition and use of the imple-mented system. The UCCM process combines change management (specifically, Kotter’s model) and user-centered design (UCD) approaches. The UCCM process is validated with a retrospective case study and a comparative evaluation. The contributions of this thesis are: • Major contribution: A user-centered change management (UCCM) process that helps healthcare organi-zations implementing a CPOE system by planning and managing the change ac-companying such implementation. The UCCM process includes: o A process that combines UCD and change management approaches. o A customizable guide that can be adjusted to meet the needs of different us-ers, organizations, and clinical settings. o A systematic change process that makes users the center of the change. o Survey examples that can help: a. Collect user requirements to improve their acceptance of the CPOE system. This survey was deployed as a pilot. b. Measure users’ satisfaction with the change management plan, after the CPOE implementation. • Minor contribution: o A list of factors that can affect users’ acceptance of the CPOE system.
Keywords: CPOE; computerized provider order entry; acceptance; change management; health information technology; UCD; user-centered design